False-positive free transparent and optimal watermarking for colour images. (26th August 2020) - Singh, Neha; Joshi, Sandeep; Birla, Shilpi
Digital image watermarking serves as a tool for protection of ownership of the media shared on common platform. This paper presents a robust, blind watermarking technique for colour images based on singular value decomposition (SVD) and discrete wavelet transform (DWT). Watermark is embedded in mid-frequency sub-bands of two-level DWT. These sub-bands are divided into non-overlapping blocks of size 4 × 4, each of which undergoes SVD. The singular values (SV) are updated based on watermark bit and using Lagrange's optimisation principle using two keys. Experiments show that the proposed technique is imperceptible with PSNR > 40 dB. Also, the technique can resist general image processing operations (attacks) on the images with the structural similarity index measure (SSIM) nearly 1 and sufficiently high bit correct ratio (BCR).